PET/CT Imaging of Activated Cancer-Associated Fibroblasts Predict Response to PD-1 Blockade in Gastric Cancer Patients - Rong, Xiaoxiang; Lv, Jinyu; Liu, Yantan; Wang, Zhaojun; Zeng, Dongqiang; Li, Yuedan; Li, Shaowei; Wu, Jianhua; Shen, Zheyu; Shi, Min; Liao, Wangjun; Wu, Zhenzhen; et al. (Frontiers in Oncology, 2022)
Background Promising development in immune checkpoint blockade (ICB) therapy has shown remarkable results in the treatment of gastric cancer (GC). However, the objective response rate in GC remains unsatisfactory. Noninvasive imaging to predict responses to ICB therapy via tumor microenvironment (TME) assessment is needed. Accordingly, this study aimed to evaluate the role of 68Ga-FAPI-04 PET/CT in the assessment of the immunosuppressive TME in GC and to cross-correlate imaging findings with responses to ICB therapy. Methods The correlation between fibroblast-activation-protein (FAP) expression and immunosuppressive cell infiltration was analyzed using The Cancer Genome Atlas (TCGA), Gene Expression Omnibus (GEO) database, and GC tissue microarrays. To characterize the TME, TMEscores were calculated based on RNA-seq data from four GC patients. A total of 21 patients with GC underwent 68Ga-FAPI-04 PET/CT before ICB treatment, and two of them were imaged after ICB therapy. Results FAP expression was found to be closely correlated with poor prognosis and infiltration of immunosuppressive cells, including myeloid-derived suppressor cells (MDSCs), exhausted T cells, and regulatory T cells (Tregs) in GC. We also found a strong relationship (R2 = 0.9678, p = 0.0162) between 68Ga-FAPI-04 uptake and TMEscore. Further analyses indicated that high 68Ga-FAPI-04 uptake was correlated with reduced therapeutic benefits from ICB therapy. Conclusions 68Ga-FAPI-04 PET/CT may be used to noninvasively image the cancer-associated fibroblasts immunosuppressive TME in vivo and also potentially serve as a predictive biomarker of survival and antitumor immune response among patients who received ICB therapies.